The Effectiveness of Aquatic Exercises in Improving Balance and Gait in Patients with Knee Osteoarthritis: A Systematic Review - Kinza Noor, Muhammad Aqdus Ahsan, Salma Bibi, Tayyaba Mumtaz (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: Knee osteoarthritis is a degenerative joint disease that primarily affects older persons. The second most common disease among adults living in communities is osteoarthritis, which also has the second-highest overall medical cost aggregate. Objective: This review aimed to synthesize evidence for the effectiveness of aquatic exercises on the mobility, balance, gait, and posture of patients with knee osteoarthritis. Method: The databases utilized for literature searching were Embase, PubMed, PEDro, Cochrane library, and web of science. The search was conducted for literature selection on electronic databases up to November 2022. The selected studies were randomized controlled trials conducted in the past 12 years and published in English. To assess the methodological quality of the selected studies, the PEDro scale for quality assessment was applied. Results: Out of 366 obtained studies from the initial search, 10 trials met the inclusion criteria and were selected for review. All the included studies were found to have good methodological quality when assessed by the PEDro scale. A total of 531 participants, 74 males, and 457 females were evaluated with ages above 40 years. The aquatic exercise sessions for 3 to 12 weeks, 2 to 5 times a week for 30 to 90 minutes were administered across the studies. Although the method, duration, and frequency of aquatic interventions varied widely regarding mobility and balance in the studies, most of the studies found significant improvement in balance, postural control, and mobility. No convincing evidence can be provided for the improvement of gait and reduction of postural sway for both genders. Conclusion: Aquatic exercises are generally effective for the management and treatment of elderly patients suffering from knee osteoarthritis and should be used as an initial treatment option. Aquatic exercises with proper protocols of warm-up, specific aquatic exercise sessions, and cool-down are effective for the improvement of mobility, balance, and postural control in patients with knee osteoarthritis. Keywords: knee osteoarthritis, osteoarthritis of the knee, knee osteoarthritides, aquatic exercise, hydrotherapy, and water exercise